Local Government Stakeholder Perceptions of Legitimacy and Conflict of Interest: The Alcohol Industry and the "Drink Free Days" Campaign in England - Helen Walls; Benjamin Hawkins; Anna Durrance-Bagale (Kerman University of Medical Sciences, 2022)
Background  Industry involvement in alcohol policy is highly contentious. The Drink Free Days (DFD) campaign (2018-2019) run by Public Health England (PHE), an executive agency of government, and Drinkaware, an industry-funded 'alcohol education charity' to encourage middle-aged drinkers to abstain from drinking on some days was criticised for perceived industry involvement. We examine the extent to which the DFD campaign was supported by local-authority Directors of Public Health (DPHs) in England - which have a statutory remit for promoting population health within their locality - and their reasons for this. Methods  Our mixed-methods approach included a stakeholder mapping, online survey, and semi- structured interviews. The stakeholder mapping provided the basis for sampling survey and interview respondents. In total, 25 respondents completed the survey, and we conducted 21 interviews with DPHs and their local authority (LA) representatives. We examined survey responses, and coded free-text survey and interview responses to identify key themes.  Results  While some respondents supported the DFD campaign, others did not promote it, or actively opposed it, due mainly to concerns about conflicts of interest and the legitimacy of industry involvement in the campaign. These were considered to undermine PHE's independence and deflect attention from more important, evidence-based policy interventions such as alcohol pricing while conferring vicarious credibility on Drinkaware. We also found low levels of knowledge about alcohol-related harm, the effectiveness of different policies to address these and the policy-influencing strategies used by the alcohol industry.Conclusion  The findings highlight the dangers of industry partnership and potential conflicts of interest for government agencies and the ineffectiveness of the campaigns they run at local and national levels. They demonstrate the need for caution in engaging with industry-associated bodies at all levels of government and are thus of potential relevance to studies of other health-harming industries and policy contexts.